Evaluation of Serum Factor H and Anti-Factor H Antibodies in Childhood Hemolytic Uremic Syndrome: A Comprehensive Review - Hany Elsayed Ibrahim, Mohamed Reda Abdelkader, Amal Saeed El Shal; Mohamed Ragab Abdellatif (Pegem Journal of Education and Instruction, 2024)
Hemolytic uremic syndrome (HUS) is a leading cause of acute kidney injury (AKI) in children, characterizedby the triad of microangiopathic hemolytic anemia, thrombocytopenia, and renal impairment. While typical HUS is oftenlinked to Shiga toxin–producing Escherichia coli (STEC), atypical HUS (aHUS) results from dysregulation of thealternative complement pathway.